2002
DOI: 10.1002/ar.10105
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional architecture of the myosalpinx in the mare as revealed by scanning electron microscopy

Abstract: The three-dimensional architecture of the myosalpinx in the mare was investigated by means of scanning electron microscopy (SEM) after removal of interstitial connective tissue with NaOH digestion. In the extramural portion of the tubo-uterine junction (TUJ), isthmus, and ampulla, the myosalpinx architecture is represented by a unique muscular structure which runs from the mesosalpinx to the base of the inner mucous folds. This unique muscular structure consists mainly of bundles of muscular fibers independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
0
2
0
2
Order By: Relevance
“…The lower presence of ciliated cells in the isthmus of mare oviduct could be related to the presence of the well-developed muscle layer surrounding the mucosa. In the mare isthmus the myosalpinx has a plexiform structure [19] which could generate a stirring movement of lumen content [20]. This process can lead to the optimization of the micro-environment and thus favourable conditions for the early embryo development during its flow to the uterus [21].…”
Section: Discussionmentioning
confidence: 99%
“…The lower presence of ciliated cells in the isthmus of mare oviduct could be related to the presence of the well-developed muscle layer surrounding the mucosa. In the mare isthmus the myosalpinx has a plexiform structure [19] which could generate a stirring movement of lumen content [20]. This process can lead to the optimization of the micro-environment and thus favourable conditions for the early embryo development during its flow to the uterus [21].…”
Section: Discussionmentioning
confidence: 99%
“…The myosalpinx is generally constituted by two muscular components: the extrinsic musculature, running within the sub-peritoneal connective tissue of the mesosalpinx, and the intrinsic musculature peculiar to the salpinx itself (Muglia and Motta, 2001). In the mare, these two components constitute a unique plexiform-type muscular structure (Germanà et al, 2002). This study revealed that in the ampulla only isolated myocytes of the intrinsic musculature expressed anti-MOR immunoreactivity (Figs.…”
Section: Discussionmentioning
confidence: 73%
“…Исследования гладкой мускулатуры маточных труб свидетельствуют о сложной и особенной структурной организации лейомиоцитов [13,[16][17][18]. Известно, что клеточная популяция гладкой мышечной ткани, интегрированная в состав различных висцеральных органов, неоднородна [5, 12,14].…”
Section: медицинская экологияunclassified
“…Выбор истмического отдела маточной трубы для данного анализа был обусловлен рядом факторов. Во-первых, именно в этом отделе мышечный слой является максимально выраженным и характеризуется наибольшей функциональной активностью [13,15,16]. Во-вторых, известно, что изменения в маточной трубе при трубной беременности имеются на ограниченном местом плацентации протяжении [1,7,22 Результаты, полученные в ходе цитологического исследования, обрабатывали методами вариационной статистики, с вычислением средних и стандартных ошибок средних (M ± m) и коэффициента вариации (V).…”
Section: методыunclassified